2022
DOI: 10.1037/xge0001127
|View full text |Cite
|
Sign up to set email alerts
|

Language shapes children’s attitudes: Consequences of internal, behavioral, and societal information in punitive and nonpunitive contexts.

Abstract: Research has probed the consequences of providing people with different types of information regarding why a person possesses a certain characteristic. However, this work has largely examined the consequences of different information subsets (e.g., information focusing on internal versus societal causes). Less work has compared several types of information within the same paradigm. Using the legal system as an example domain, we provided children (N=198 6to 8-year-olds) with several types of information-includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Any family with eligible children could participate. As in other studies (e.g., Dunlea & Heiphetz, in press; Marshall et al, 2020), recruitment method did not reliably predict children's responses. All children received a small prize such as a sticker.…”
Section: Methodssupporting
confidence: 47%
“…Any family with eligible children could participate. As in other studies (e.g., Dunlea & Heiphetz, in press; Marshall et al, 2020), recruitment method did not reliably predict children's responses. All children received a small prize such as a sticker.…”
Section: Methodssupporting
confidence: 47%
“…Social learning theory posits that children are influenced by attitudes that adults convey (Bandura, 1971; Ma et al, 2018; Rhodes et al, 2012), and linguistic cues are an important mode of transmission of essentialist beliefs about people (Gelman & Heyman, 1999; Gelman et al, 2010; see Dunlea & Heiphetz, 2021). For example, Gelman and Heyman (1999) found that 5‐ and 7‐year‐old children judged novel descriptions of people (such as that someone eats carrots) in a more essentialized way when identified with a noun label (e.g., she is a carrot‐eater ) than with a verbal predicate (e.g., she eats carrots whenever she can ).…”
mentioning
confidence: 99%
“…Children's tendency to engage in internal thinking about, for example, economic success (Mistry et al., 2021), classroom achievement (Goudeau & Cimpian, 2020), or gender differences in occupation (Garrett et al., 1977) can have negative consequences, including perceiving disadvantaged groups negatively and supporting initiatives and engaging in behaviors that maintain inequity and distance between groups (see Diesendruck & Menahem, 2015; Dunlea & Heiphetz, 2022; Hussak & Cimpian, 2015; Mandalaywala et al., 2018; Roberts et al., 2017; Sidanius & Pratto, 1999; Williams & Eberhardt, 2008). Since young children's beliefs in a variety of domains can become ingrained with long‐lasting consequences (Shtulman & Harrington, 2016; Shtulman & Valcarcel, 2012), children's internal thinking about social inequities may be particularly damaging because such thinking can persist into adulthood.…”
Section: Causes and Consequences Of Internal Thinkingmentioning
confidence: 99%